Benefit–risk assessment of rivaroxaban versus enoxaparin for the prevention of venous thromboembolism after total hip or knee arthroplasty - Levitan, Bennett (Dove Medical Press, 2014)
PURPOSE: Venous thromboembolism is a common complication after major orthopedic surgery. When prescribing anticoagulant prophylaxis, clinicians weigh the benefits of thromboprophylaxis against bleeding risk and other adverse events. Previous benefit–risk analyses of the REgulation of Coagulation in ORthopaedic surgery to prevent Deep vein thrombosis and pulmonary embolism (RECORD) randomized clinical studies of rivaroxaban versus enoxaparin after total hip (THA) or knee (TKA) arthroplasty generally used pooled THA and TKA results, counted fatal bleeding as both an efficacy and a safety event, and included the active and placebo-controlled portions of RECORD2, which might confound benefit–risk assessments. We conducted a post hoc analysis without these constraints to assess benefit–risk for rivaroxaban versus enoxaparin in the RECORD studies. PATIENTS AND METHODS: Data from the safety population of the two THA and two TKA studies were pooled separately. The primary analysis compared the temporal course of event rates and rate differences between rivaroxaban and enoxaparin prophylaxis for symptomatic venous thromboembolism plus all-cause mortality (efficacy events) versus nonfatal major bleeding (safety events). Additionally, these rates were used to derive measures of net clinical benefit, number needed to treat (NNT), and number needed to harm (NNH) for these two end points. RESULTS: After THA or TKA, and compared with enoxaparin, rivaroxaban therapy resulted in more efficacy events prevented than safety events caused, with benefits exceeding harms early and throughout treatment and follow-up. Relative to enoxaparin, rivaroxaban treatment prevented six efficacy events per harm event caused for THA, with NNT =262/NNH =1,711. For TKA, rivaroxaban treatment prevented four to five efficacy events per harm event caused, with NNT =102/NNH =442. Sensitivity analysis that included surgical-site bleeding resulted in NNH =345 for THA and NNH =208 for TKA. CONCLUSION: In the RECORD studies, considering death, symptomatic venous thromboembolism, and major bleeding, rivaroxaban resulted in greater benefits than harms compared with enoxaparin. When incorporating surgical-site bleeding, rivaroxaban also results in greater benefit than harm for TKA and is balanced with enoxaparin for THA.